Navegando a medicina com uma mente atípica: um estudo de caso autoetnográfico sobre os desafios do TDAH na graduação médica da UFSCar - Oliveira, Vinícius Mesquita de (Universidade Federal de São Carlos, 2025)
This undergraduate thesis is a critical-reflective narrative, prepared in accordance with the guidelines of the Pedagogical Policy Project of the medical program at the Federal University of São Carlos. It aims to present the trajectory and experiences of this student-author during the undergraduate medical course. The narrative is structured as an autoethnography, exposing, from the student's perspective and experience, the learning challenges of a student with a late diagnosis of Attention Deficit Hyperactivity Disorder (ADHD) in the medical program at the Federal University of São Carlos. Within the scope of this work, a discussion on neurodivergence is essential, given the significant social and pedagogical challenges we face with the population segment referred to as neurodivergent.
Navigating medicine with an atypical mind: an autoethnographic case study on the challenges of ADHD in medical school at UFSCar
Keywords: narrativa crítico-reflexiva; neurodivergente; autoetnográfica; critical-reflective narrative; neurodivergent; autoethnography; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA; 4. Educação de Qualidade